Bone healing pattern in surgically created circumferential defects around submerged implants: an experimental study in dog - Rossi, Fabio [UNESP]; Botticelli, Daniele [UNESP]; Pantani, Fabio [UNESP]; Pereira, Flavia Priscila [UNESP]; Salata, Luiz Antonio; Lang, Niklaus P. (Wiley-Blackwell, 2012)
Objective: To describe the healing of marginal defects below or above 1 mm of dimension around submerged implants in a dog model.Material and methods: In 12 Labrador dogs, all mandibular premolars and first molars were extracted bilaterally. After 3 months of healing, full-thickness flaps were elevated in the edentulous region of the right side of the mandible. Two recipient sites were prepared and the marginal 5mm were widened to such an extent to obtain, after implant installation, a marginal gap of 0.5mm at the mesial site (small defect) and of 1.25mm at the distal site (large defect). Titanium healing caps were affixed to the implants and the flaps were sutured allowing a fully submerged healing. The experimental procedures were subsequently performed in the left side of the mandible. The timing of the experiments and sacrifices were planned in such a way to obtain biopsies representing the healing after 5, 10, 20 and 30 days. Ground sections were prepared and histomorphometrically analyzed.Results: The filling of the defect with newly formed bone was incomplete after 1 month of healing in all specimens. Bone formation occurred from the base and the lateral walls of the defects. A larger volume of new bone was formed in the large compared with the small defects. Most of the new bone at the large defect was formed between the 10- and the 20-day period of healing. After 1 month of healing, the outline of the newly formed bone was, however, located at a similar distance from the implant surface (about 0.4mm) at both defect types. Only minor newly formed bone in contact with the implant, starting from the base of the defects, was seen at the large defects (about 0.8mm) while a larger amount was detected at the small defects (about 2.2 mm).Conclusion: Marginal defects around titanium implants appeared to regenerate in 20-30 days by means of a distance osteogenesis. The bone fill of the defects was, however, incomplete after 1 month.
Keywords: animal study; bone; bone healing; defect; histomorphometry; implant dentistry; osseointegration; submerged healing